Spontaneous Pneumothorax - Sebayang, Abed Nego Okthara; Kurniawan, Setiadi Drajad (Talenta Publisher, 2022)
Background: Pneumothorax is a medical emergency which is defined as an abnormal condition where there is air in the pleural cavity which physiologically contains only a small amount of fluid. Pneumothorax can arise spontaneously or as a result of trauma. Method: The method used in this study is a literature review. The literature study conducted by the author is by searching various written sources, whether in the form of books, archives, magazines, articles and journals, or documents that are relevant to the problem being studied. Discussion: Pneumothorax is classified as primary spontaneous if it occurs in the absence of basic lung disease or thoracic trauma. Pneumothorax is classified as secondary spontaneous if it is caused by basic lung disease. The etiology of primary spontaneous pneumothorax is pleural bleb and bulla. A bleb (air pocket) or bulla is a small air-filled pocket that forms between the lung and pleural tissues. The risk factors associated with pneumothorax are smoking and body thinness. Conclusion: The initial management of spontaneous pneumothorax includes emergency management. Furthermore, management can be divided into conservative and invasive management